Media Violence as the Production of Meaning: Toward a Philosophical Approach — A Comparative Study between Pierre Bourdieu and Jean Baudrillard and Its Practical Applications - سمير رزيق (International Journal of Social Communication, 2025)
The article examines media violence in Pierre Bourdieu and Jean Baudrillard as a process of meaning production rather than merely harmful content. It also calls for slowing the editorial pace in favor of verification and explanation; making selection criteria public and broadening pluralism in sources and angles; deconstructing ideologized labels and sensational headlines; and institutionalizing critical media–visual literacy that distinguishes events from spectacle. Finally, it offers a field-testable conceptual framework for understanding media violence as both symbolic and visual domination.